Instrument for Student Attitudes Assessment in Science Learning: A Review and Bibliometric Analysis - Dini Rosdiane Rusdiyanto; Bibin Rubini; Didit Ardianto (Jurnal Pendidikan Indonesia Gemilang, 2023)
This research aimed to provide a bibliometric study on the keyword "Attitude assessment instrument." The method used in this study is a quantitative method to use metadata harvesting stages using the Publish or Perish (PoP) software from the Google Scholar database. 6 relevant journals have been found out of 97 articles search results in the Google Scholar database. The searches were sorted from 2016 to 2021 and then analyzed in this study. The selected references are used as a database which is then hidden and visualized using the VOSviewer software. In general, this study provides a suitable reference point for further research on the "Attitude assessment instrument."